Continuous immobilization of lead by biomineralization in a fluidized-bed biofilm reactor. (15th December 2022) - Li, Xiao; Zhang, Kejing; Xue, Yingwen
Abstract: Microbial-induced phosphate precipitation (MIPP) is a promising biomineralization technology to immobilize lead in wastewater. However, more in-depth biological principles and reactor models with more biomass need to be further explored to guide its engineering applications. In this study, a fluidized-bed biofilm reactor with biomineralization capability was proposed for immobilizing lead continuously and circularly. The optimal operating parameters for the reactor stages of start-up, operation and circulation were investigated. Stable biofilms could be formed by circulating Lysinibacillus suspension into the column containing the polypropylene fiber with the addition of montmorillonite. Its lead removal efficiency reached above 80% within 3 h and decreased to 23% after 12 h continuous operation. Besides, the reactor could maintain a high lead removal efficiency after multiple elutions and had a better performance without secondary pollution in treating practical wastewater due to the organic matter contained. The functional bacteria stability of the dominant position and functions was the main reason for keeping high removal efficiency during the process. This research provided an effective method for the engineering application of biomineralization for lead removal. Graphical abstract: Image 1 Highlights: The fluidized bed biofilm reactor was proposed to continuously immobilize lead. Montmorillonite could enhance the bacterial adhesion to the polypropylene fiber. The influence factors in operating and recycling processes were investigated. The reactor maintained a high removal efficiency after several elutions. Organic matters contained make a better removal performance in practical wastewater.